The Notion of 'Being Informative' & the Praxiological-Information Perspective on Language - Antonio Florio (tripleC: Communication, Capitalism & Critique)
After a concise introduction on the analysis of truth and meaning in philosophy of language two notions of information are grasped by the analysis of Situation Semantics and Situation Theory. The first is that of correlation, the second that of constraint; the latter is reducible to the former. More than that, the phenomenon of ";alethic nature of information"; is highlighted and the notion of ";being informative"; is pointed out. The difference between a meaning-oriented and an informational-oriented perspective of language is marked. Messages are recognized as being the atomic constituents of the informational perspective of language; the architecture of language is shown; and a praxiological-information perspective on the study of language is outlined.